TRILEMMA OF THE STRATEGIC CHOICE OF UKRAINE IN CONDITIONS OF ECONOMIC GLOBALIZATION - Sharov, Oleksandr (Journal of European Economy, 2017)
Analysis of the criteria of choice of integration direction of Ukraine’s economy development within the framework of modern globalization is conducted. Some of issues of the problem were considered by the number of authors, such as I. Burakovskyi, A. Veselovskyi, A. Goncharuk, K. Hryshchenko, S. Tolstov, A. Shapovalova, R. Shpek etc. The author indicates the subjective and objective requirements regarding the different integration strategies and makes a conclusion concerning lack of options of Eurointegration direction, which is understood not as an aspiration to obtain a EU full-membership but as a provision of correspondence of European standards to the internal conditions of economic activity.